Pattern of Students’ (Akhlak) Character Building through Student Organization Activity: A Study of Nature Lover Student (MAPALA) in Islamic University - Oviyanti, Fitri; Rochmiyatun, Siti; Fauzi, Muhamad; Bujuri, Dian Andesta (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to reveal good practices in (akhlak) character building pattern through the activities of the Student Organization for Nature Lover (MAPALA) at an Islamic University in Palembang, South Sumatra. This research uses a qualitative case study type method. Research data was obtained through interviews, observation and documentation. There were 14 informants involved in this research. They are Vice Chancellor 3 for student affairs, Deputy Dean 3 (MAPALA coordinator), Chair of MAPALA, Deputy Chair of MAPALA, alumni (seniors) of MAPALA, 6 student members of MAPALA, and 3 lecturers. Research data was analyzed using an interactive model of three techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research show that the development of student character through the first extracurricular activities of the Student Activity Unit (UKM) for Nature Lovers Student (MAPALA), cognitive development activities, which include public discussions, up-greading, seminars, wildlife crime investigation training, and get-to-know interviews. Medan. Second, affective coaching activities, which include Capital Care Fundraising, Mosque Cleaning, Tiger Day Commemoration, and recital. Third, psychomotor development activities, which include Camping, Mountain Expeditions, Adventure with MAPALA, Young Member Adventures, Exercise and Rock Climbing. These activities have a positive impact on developing student character. Through these activities, students are taught to be religious, honest, communicative, environmentally conscious, socially caring and love nature.